2007
DOI: 10.1084/jem.20060465
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 is critical for self-renewal of hematopoietic stem cells

Abstract: Members of the transforming growth factor β (TGF-β) superfamily of growth factors have been shown to regulate the in vitro proliferation and maintenance of hematopoietic stem cells (HSCs). Working at a common level of convergence for all TGF-β superfamily signals, Smad4 is key in orchestrating these effects. The role of Smad4 in HSC function has remained elusive because of the early embryonic lethality of the conventional knockout. We clarify its role by using an inducible model of Smad4 deletion coupled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…In contrast, specific loss of Smad4 in MPs compromises myogenic differentiation during embryonic skeletal muscle development (Han et al, 2012). Additionally, consistent with the critical role for Smad4 in stem and progenitor cell function, targeted deletion of Smad4 in hematopoietic, hair follicle, and neural stem and derived progenitor cell populations leads to their depletion during homeostasis and regeneration (Karlsson et al, 2007; Yang et al, 2009; Mira et al, 2010). Moreover, targeted loss of Smad4 in myofibers leads to modest deterioration during growth and aggravation of denervation-induced atrophy in adults (Sartori et al, 2013).…”
Section: Introductionmentioning
confidence: 68%
“…In contrast, specific loss of Smad4 in MPs compromises myogenic differentiation during embryonic skeletal muscle development (Han et al, 2012). Additionally, consistent with the critical role for Smad4 in stem and progenitor cell function, targeted deletion of Smad4 in hematopoietic, hair follicle, and neural stem and derived progenitor cell populations leads to their depletion during homeostasis and regeneration (Karlsson et al, 2007; Yang et al, 2009; Mira et al, 2010). Moreover, targeted loss of Smad4 in myofibers leads to modest deterioration during growth and aggravation of denervation-induced atrophy in adults (Sartori et al, 2013).…”
Section: Introductionmentioning
confidence: 68%
“…Smad5 is supposed to mediate BMP signals [149]; Forced Smad7 expression may increase the self renewal capacity [150] or modulate fate decision [151]. Smad4 appears to be critical for self renewal possibly by participating in Wnt and Notch signaling [152,153]. Finally, osteopontin, a matrix glycoprotein synthesized by osteoblast is a negative regulator of HSC.…”
Section: The Contribution Of the Niche To Signaling In Adult Stem Cellsmentioning
confidence: 97%
“…[63] Smad4 −/− HSCs surprisingly possess normal proliferation. Colony and single-cell proliferation assays demonstrated that clonogeneicity and proliferation of hematopoietic progenitors in vitro are unaffected by Smad4 deficiency.…”
Section: Smad Signaling Pathwaymentioning
confidence: 99%
“…Under these conditions, recipients of Smad4 −/− BM cells have 4-fold lower hematopoietic reconstitution than WT donor cells, although their lineage distribution output remains normal. [63] Intriguingly, these results may be due to lower proliferation capacity of Smad4 −/− HSCs under regenerative conditions, although the difference is very modest. Hence, in this case, a permanent reduction in Smad4 signaling in vivo does not enhance HSC proliferation, as it may have been expected; but it still leads to loss of HSC functions.…”
Section: Smad Signaling Pathwaymentioning
confidence: 99%